2016
DOI: 10.1002/dmrr.2780
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with a co‐expression DNA plasmid containing GAD65 fragment gene and IL‐10 gene induces regulatory CD4+ T cells that prevent experimental autoimmune diabetes

Abstract: Our data suggested that SGAD65190-315 /IL-10 DNA vaccine had protective effects on T1D by upregulating autoantigen-reactive Tregs. Our findings may provide a novel preventive therapy for T1D. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 57 publications
(73 reference statements)
1
14
0
Order By: Relevance
“…CD4 + CD25 + Foxp3 + Treg cells have recently been considered as powerful mediators to re-balance of Th1/Th2 in autoimmune diabetes ( Liu et al, 2016 ). Moreover, Saunders et al (2007) showed that T. spiralis infection delays the onset and prevents the progression of T1DM.…”
Section: Trichinella -Derived Molecules: a Panacea For Moder...mentioning
confidence: 99%
“…CD4 + CD25 + Foxp3 + Treg cells have recently been considered as powerful mediators to re-balance of Th1/Th2 in autoimmune diabetes ( Liu et al, 2016 ). Moreover, Saunders et al (2007) showed that T. spiralis infection delays the onset and prevents the progression of T1DM.…”
Section: Trichinella -Derived Molecules: a Panacea For Moder...mentioning
confidence: 99%
“…An important insight from these studies is the observation that the secreted version of the polypeptide containing all epitopes has therapeutic benefit, but not the version in which peptides are targeted intracellularly. On the one hand, this is reminiscent of another DNA vaccine study in which the long GAD65190-315 peptide was more protective when secreted than the full non-secreted GAD65 protein in NOD mice (40). On the other hand, we have shown that both secreted and non-secreted forms induced immune responses in draining lymph nodes (23).…”
Section: Discussionmentioning
confidence: 61%
“…To verify that IL16 could regulate the infiltration of CD4+ CD25+ Foxp3+ Tregs, we used recombinant IL16 to stimulate lymphocytes. IL10 is known to significantly increase the number of CD4+ CD25+ Tregs [ 26 ]. Therefore, lymphocytes were stimulated with recombinant IL10 as the positive control group.…”
Section: Resultsmentioning
confidence: 99%